The Roermond mausoleum. Archeology of a tomb (Bulletin KNOB, 2016)
Gerard van Gelre († 1229) and his wife Margaretha van Brabant († 1231) were the founders of a Cistercian convent in Roermond and as such were entitled to be buried in the city’s main church, the Munsterkerk. Their tombs are below the dome, in the crossing of a cloverleaf-shaped choir. An investigation of the underground burial chamber led to the conclusion that no mausoleum had been erected above the tombs at the time of burial. The princely couple were nevertheless honoured with a memorial in the form of stone statues, as was customary in the Romanesque period. The mausoleum that graces the Munsterkerk today, was designed and built a generation later, probably around 1270. For princely and noble families in that period, a tomb with an effigy of the deceased was a sign of their social status.Those who commissioned the Roermond mausoleum saved themselves the expense of an effigy and content themselves with reusing the existing statues by simply placing them horizontally on the base pre pared for that purpose. The statues were converted into recumbent figures, which bear the unmistakable scars of this operation. The humped pieces against which their feet rest are the plinths that originally held the statues in an upright position. Separate stone cushions had to be inserted under the heads. Such incongruities are not the work of a sculptor who fashioned these memorials all at the same time. From an art-historical perspective, the Roermond effigies belong to the typology of the imperial statues of the Romanesque and pre-Romanesque periods. The hitherto prevailing view, that the Roermond figures were the earliest known husband and wife effigies, is accordingly no longer tenable. Another notion, which posited a relation between the mausoleum and the architectural scheme of the trilobate choir, whereby the church could be regarded as a ‘funerary church’, is likewise no longer tenable because the design of the church building predates that of the mausoleum by some fifty years.